Long-Term Efficacy and Safety of RNAi-Mediated Virus Resistance in ‘HoneySweet’ Plum - Singh, Khushwant; Callahan, Ann M.; Smith, Brenda J.; Malinowski, Tadeusz; Scorza, Ralph; Jarošová, Jana; Beoni, Eva; Polák, Jaroslav; Kundu, Jiban Kumar; Dardick, Chris (Frontiers in Plant Science, 2021)
Interfering RNA (RNAi) technology has been established as an effective strategy to protect plants against viral infection. Despite this success, RNAi has rarely been applied due to the regulatory barriers that confront genetically engineered plants and concerns over possible environmental and health risks posed by non-endogenous small RNAs. ‘HoneySweet’ was developed as a virus resistant plum variety that is protected by an RNAi-mediated process against Sharka disease caused by plum pox virus. ‘Honeysweet’ has been approved for cultivation in the United States but not in countries where plum pox virus is endemic. Here we evaluated the long-term efficacy of virus resistance in ‘Honeysweet’, the nature and stability of its sRNA profile, and the potential health risks of consuming ‘HoneySweet’ plums. Graft infected ‘Honeysweet’ trees carrying large non-transgenic infected limbs remained virus free after >10 years in the field and viral sequences from the non-transgenic infected limbs showed no evidence of adaptation to the RNAi-based resistance. Small RNA profiling revealed that transgene-derived sRNA levels were stable across different environments and on average were >10 times lower than those present in symptom-less fruit from virus infected trees. Comprehensive 90-day mouse feeding studies showed no adverse health impacts in mice and there was no evidence for potential siRNA off-target pathologies predicted by comparisons of the most abundant transgene derived sRNAs to the mouse genome. Collectively, the data confirm that RNAi provides a highly effective, stable, and safe strategy to combat virus diseases in crop plants.